Analysis of temperature field and noise characteristics of impinging jet of carrier-based aircraft engine - Longzhou QI; Heying FENG; Yehui PENG; Kun ZHAO (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesAs the deflection angle has great influence on temperature and noise radiation near the deflector of the impinging jet of a carrier-based aircraft, determining an appropriate deflection angle can expand the safe area around the aircraft.MethodsThis paper analyzes the flow field, temperature field and sound field characteristics near the deflector of a certain type of engine tail nozzle in full afterburner conditions under different deflection angles (β=35°, 45°, 55°) and different monitoring distances (S=20D, 30D, 50D, 80D). Using large eddy simulation (LES) and acoustic analogy methods, a calculation model of a supersonic jet impinging on an inclined plate is established, and the correctness of the model verified by experimental data.ResultsThe deflection angle changes the distribution of the temperature field. When β=45°, the deflector has a better effect, personnel and equipment behind the deflector can be protected most effectively, and the high-temperature reflux on the countercurrent side of the deflector will affect the carrier aircraft. The rear wheel basically has no effect. The deflection angle also has great influence on far-field radiated noise. When noise monitoring distance S=40D, the total sound pressure level increases with the increase of the deflection angle. When β=35°, the noise radiation range affecting the normal work of personnel is at its smallest.ConclusionsIn general, when β=45°, personnel and equipment near the deflector suffer the least high temperature and noise threat. Even so, in order to ensure that the ground crew can work normally at any angle, the tail nozzle should be kept above 80D.